Elevated plasma/serum levels of prolactin in patients with systemic sclerosis: A systematic review and meta-analysis. Issue 38 (18th September 2020) - Wu, Yang; Li, Meng-Lei; Han, Hua-Jing; Huang, Li-Jun; He, Yong
Abstract: Background: Prolactin (PRL), an inflammatory hormone with cytokine properties, has long been considered to play a crucial role in the pathogenesis of autoimmune diseases, including systemic sclerosis (SSc). However, the plasma/serum levels of PRL in SSc were inconsistent in published studies. The aim of this study was to evaluate the plasma/serum levels of PRL in patients with SSc accurately. Methods: Electronic databases, including PubMed, EMBASE, Cochrane Library, CNKI, VIP and WANFANG databases, were searched up to October 15, 2019. Pooled standard mean difference (SMD) with 95% confidence interval (CI) was calculated by fixed-effect or random-effects model analysis. All statistical analyses were conducted with STATA 12.0. Results: Fifty three articles were obtained after searching databases, and 9 studies with 293 SSc patients and 282 controls were finally included. The meta-analysis showed that the plasma/serum PRL level in SSC patients was significantly increased compared with the healthy controls, with the SMD of 1.00 and 95% CI (0.56, 1.43). Subgroup analysis showed that female patients had higher plasma/serum PRL levels. However, no significant change in plasma/serum PRL levels was observed in male patients ( P  = .318). In subgroup analysis by detection type, electrochemiluminescence immunoassay (ECLIA) group and enzyme-linked immunosorbent assay (ELISA) group showed higher PRL levels among SSc patients. Conclusions: In summary, our meta-analysis showed a significantly higher plasma/serum PRL level in SSc patients than healthy controls, and it was associated with gender and detection method.